Ритуал закликання зими пастухами в Литві - Мікштайте-Чичюркене, Р. (Народна творчість та етнологія, 2011)
The article describes the winter calling ritual performed by Lithuanian herders. In this article author tries to formulate a new hypothesis of the Muslim-Tatar origin of this ritual.